Cultural Self-Awareness as Awareness of Culture's Influence on the Self: Implications for Cultural Identification and Well-Being. (June 2018) - Lu, Chieh; Wan, Ching
Cultural self-awareness refers to the awareness of how culture has influenced the self. This research investigated how such awareness might be related to cultural identification and well-being. In Study 1, we developed a scale measure that differentiated individuals' awareness of how culture has influenced them (cultural self-awareness) and how their own personality and personal experiences have influenced them (personal self-awareness). Factor analysis and item analysis showed a two-factor model with acceptable scale reliability. Study 2 showed that cultural self-awareness positively predicted well-being through higher cultural identification, whereas personal self-awareness positively predicted well-being through higher behavioral authenticity. Study 3 manipulated the valence of individuals' cultural experience. The indirect effect of cultural self-awareness on well-being was stronger when cultural experience was positive (vs. negative). Study 4 provided a specific cultural context for the well-being measures and replicated the findings of Studies 2 and 3. Implications on the link between culture and self were discussed.